Xylitol: Bioproduction and Applications-A Review - Umai, Devasena; Kayalvizhi, Ramalingam; Kumar, Vinod; Jacob, Samuel (Frontiers in Sustainability, 2022)
Xylitol, a natural compound classified as a sugar alcohol, is found diversely in fruits and vegetables in small quantities. Commercial production of xylitol has expanded due to its health benefits and wide applications as an alternative sweetener in food and pharmaceutical products. Production of xylitol on large scale is industrially being achieved by the chemical method. However, the biotechnological method offers the possibilities of lowered cost and energy compared to the chemical methods. It involves the conversion of xylose to xylitol by microbes or enzymes which is environmentally safe. This review highlights the prospects of the biotechnological method of xylitol production. Various microorganisms that have been used to produce xylitol, the bioprocess parameters, and genetic modifications to increase xylitol yield have been reviewed. In addition, the applications, benefits, and safety concerns to health have been discussed.